Lâminas hídricas complementares na cultura da figueira utilizando irrigação por gotejamento - Silva, Maria Clara Araujo (2012)
The culture of the fig tree fits in different climatic conditions, as long as it provides favorable conditions for the region where it is deployed, such as appropriated management. Even being adapted to different climate and soil conditions, the cultivation of the fig tree is sensible to water scarcity, if appropriate, the use of irrigation. In this sense, this study aims to evaluate the behavior of the fig tree culture (Ficus carica L) submitted to the application of different depths of irrigation water. The experiment was conducted at the Horticulture Sector of Polytechnic College, at Federal University of Santa Maria. The culture of the fig tree was in the sixth year of production and was observed from August, 2010, to June, 2011. The experiment consisted on five treatments with 7 replications, with randomized block experimental delineation, considering an adult plant per plot. The irrigation system consisted on localized drip irrigation, comprising a half-moon shape in rows around each plant. For the irrigation management, the evapotranspiration calculated by Penman equation was adopted as reference, in order to calculate the crop maximum evapotranspiration, using the Kc of 0.47. Reaching evapotranspiration of 20 mm, the irrigation was performed by applying the depth of 20 mm, corresponding to the 100% treatment, 15 mm for the 75% treatment, 10 mm to 50% treatment and 5mm to 25% treatment. The harvesting began on January 10, 2011, in other words 149 days after production pruning, starting the collection of data. Therefore, it was analyzed the following variables of production: productivity (ton.ha-1), weight (g), number and diameter of ripe figs (mm). To the classification of figs, such variables were determined: diameter (mm) and width (mm) of ripe figs. Sampling and data collection lasted 140 days, and the harvesting ended on May 28, 2011. After data collection, the information was subjected to variance analysis, submitted to the t test for multiple comparison of means in a10% level of probability, such as regression analysis. It was concluded that the fig tree was not influenced by the water levels for mean weight and mean diameter of figs variables, however the mean weight ranged from 54.78 to 57.39 g and the diameter ranged from 47.19 to 48, 37 mm. In relation to the number of fruits, differences were observed on the 100% treatment of Etc., resulting on an estimated maximum number of fruits of 292 fruits per plant. The yield responded significantly to the application of different irrigation levels, reaching maximum values of 30.61 ton ha-1, with depth corresponding to 100% of maximum crop evapotranspiration (160 mm). The figs were classified as medium, regarding that treatments did not influence the classification. The efficiency of water use showed better results with the depth equivalent to the 25% treatment of ETc, with an estimated 0.74 kg ha-1 mm-1. Regarding the results presented for the Roxo de Valinhos fig tree variety under different levels of drip irrigation in this experiment, it is possible to conclude that the most suitable depth for the culture, when it comes to the production increasement, is the additional water depth of 160 mm (100 % ETc). Although, concerning the water use efficiency, the water slide of 25% of ETc was the most efficient. For classification of ripe fruits, the irrigation showed no significant difference.